Occurrence of five nematode species from some Red Sea fishes, Yemen - Al-Zubaidy, A.B.; Mhaisen, F.T.; Abker, M.A.M. (Mesopotamian Journal of Marine Sciences, 2022)
Between September 2010 and May 2011, a total of 228 specimens belonging to 11 different species of marine fishes were collected from Al-Mehwat fish market at Hodeidah city, Yemen, to be investigated for nematode infections. Five species of nematodes, belonging to three families, were detected. These were the adult form of Cucullanus bourdini Petter and Le Bel, 1992 and the third larval stages of Anisakis simplex (Rudolphi, 1809), Terranova sp., Hysterothylacium sp. and Echinocephalus overstreeti Deardorff & Ko, 1983. C. bourdini was recorded from three fish species, A. simplex from all the eleven examined fish species, Hysterothylacium sp. from eight fish species, while both Terranova sp. and E. overstreeti were recorded from one fish species only. Adult nematodes were detected from fish intestine, while the larval parasites were detected from fish body cavity, mesenteries, stomach, intestine, liver, spleen, gonads and kidneys. For each parasite species, the prevalence, mean intensity and abundance were calculated for each infected host species. C. bourdini, Terranova sp. and Hysterothylacium sp. are recorded here for the first time from the Red Sea fishes of Yemen, while A. simplex and E. overstreeti were previously reported from some Red Sea fishes of Yemen. Among these five parasites, both A. simplex and Hysterothylacium sp. are known to have zoonotic importance